Evaluation of flow resistance in smooth rectangular open channels with modified Prandtl friction law - Cheng, Nian-Sheng (2012)
Flow resistance in open channels is usually estimated by applying the approach that is developed originally for pipe flows. Such estimates may be useful for engineering applications but always differ from measurements to some extent. This paper first summarizes empirical approaches that have been proposed in the literature to reconcile the resistance difference. These include various modifications of the pipe friction for applications to rectangular ducts and open channel flows. An improved friction equation is then derived for evaluating flow resistance of smooth rectangular open channels. Comparisons are made with experimental data reported by previous researchers and those collected in the present study. It is shown that the new proposed equation is applicable for both narrow and wide channels and is more accurate than those available in the literature.